Flow experience and mindfulness state in elite swimmers - Thienot, E.; Bernier, M.; Fournier, J. (12ème congrès de l'International Society of Sport Psychology - 2009 - Marrakech, Maroc, 2009)
The purpose of this study was to explore flow experience in elite swimmers using a qualitative investigation. Although the results supported the model of the nine conceptual dimensions of Jackson and Csikszentmihalyi (1999), a new characteristic emerged which was an awareness and acceptance of the bodily sensations in the pre-performance moments. This particular mental state seems similar to the mindfulness state, which is defined originally as the non-judgmental focus of one`s attention on the experience that occurs in the present moment (Kabat-Zinn, 1994).